Как пробудить уверенность в себе: 50 простых правил - Сергеева Оксана (Психология. Все по полочкам., 2012)
Экземпляры: (20120516) / Инвентарный номер: 47584 / Цена: 232.27 / Сис.шифр: 88.53 47584 / Авт.знак: С 32 / ББК: 88.53